The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1097/nmd.0000000000001555
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction

Abstract: Food addiction is associated with dysfunctions in the reward circuit, such as hyperresponsiveness during the exposure to high-calorie flavors in overweight and obese individuals. Similar to drug addiction, there is also impaired self-regulatory control supported by deregulation of the frontostriatal circuit. The inclusion of validated measures of food addiction in clinical research, such as the Yale Food Addiction Scale, has increased the understanding of the clinical utility of this concept. Furthermore, food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Consistent with our findings, previous studies have linked socio-demographic, health status, and lifestyle characteristics with individual risk behaviors. Specifically, younger age was shown to be a determinant of SUD [ 50 ], FA [ 18 , 19 ], and IA [ 16 , 17 ], respectively; adverse childhood experiences were shown to be a determinant of SUD [ 20 ]; poor dietary quality or disordered eating have been associated with alcohol use [ 51 ], FA [ 52 , 53 ], and IA [ 54 , 55 ], respectively; not being of normal weight has been associated with FA [ 19 , 24 , 56 ] and IA [ 25 ], respectively; smoking has been associated with AUD [ 29 ], FA [ 31 , 32 ], and IA [ 33 ], respectively; alcohol use has been associated with ND [ 29 ] and IA [ 34 ]; finally, presence of other mental health conditions has been associated with SUD [ 50 ], FA [ 23 , 24 , 27 , 56 ], and IA [ 28 ], respectively. The clustering of determinants has been evoked by descriptive studies showing a positive association of occupational sitting time with education and income [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, previous studies have linked socio-demographic, health status, and lifestyle characteristics with individual risk behaviors. Specifically, younger age was shown to be a determinant of SUD [ 50 ], FA [ 18 , 19 ], and IA [ 16 , 17 ], respectively; adverse childhood experiences were shown to be a determinant of SUD [ 20 ]; poor dietary quality or disordered eating have been associated with alcohol use [ 51 ], FA [ 52 , 53 ], and IA [ 54 , 55 ], respectively; not being of normal weight has been associated with FA [ 19 , 24 , 56 ] and IA [ 25 ], respectively; smoking has been associated with AUD [ 29 ], FA [ 31 , 32 ], and IA [ 33 ], respectively; alcohol use has been associated with ND [ 29 ] and IA [ 34 ]; finally, presence of other mental health conditions has been associated with SUD [ 50 ], FA [ 23 , 24 , 27 , 56 ], and IA [ 28 ], respectively. The clustering of determinants has been evoked by descriptive studies showing a positive association of occupational sitting time with education and income [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a review reported the co-existence of SUD and IA [ 34 ]; a cross-sectional study including 36,309 adults revealed a significant association between AUD and ND [ 29 ]. In a systematic review and meta-analysis including cross-sectional and prospective studies, eating underscored by a loss of control and binge eating disorders, which are highly correlated with FA [ 56 , 60 , 61 ], were reported to be associated with IA [ 54 ]. A cross-sectional study also suggested significant associations between problematic Internet use and eating disorders in both males and females [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Comportamiento alimentario problemático: Adoptar hábitos alimentarios excesivos, como la bulimia, la anorexia o la alimentación compulsiva, puede tener graves consecuencias para la salud (Florio et al, 2022;Hauck et al, 2020). 66.…”
Section: Conductas Adictivas En Los Adolescentesunclassified